GOALS AND TASKS OF MOTHER LANGUAGE TEACHING METHODOLOGY BASED ON LINGUOCOGNITIVE APPROACH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article is written about the goals and objectives of the mother tongue teaching methodology based on the linguocognitive approach. Uzbek formal linguistics solved a number of pressing issues of its time and created a foundation for a new linguistics, which uses the achievements of formal linguistics, works with dialectical principles, observes the relationship between language and thought, is interested in the description of linguistic and speech phenomena, and functionalizes them. - gave place to Uzbek substantive linguistics, which tried to explain the lack of interpretation with the methods of structural analysis. The representatives of this linguistics were engaged in studying and implementing the methods of events in terms of the relationship between language and speech, language-thought connection, internal capabilities of language and their language-speech differentiation. Work was done on the basis of dialectical principles (generality, essence, possibility, cause - language and its units; individuality, event, reality, consequence - speech and speech units).